KONSEP PUASA AL-GHAZALI DALAM MENUMBUHKAN KARAKTER RELIGIUS PESERTA DIDIK (STUDI PUSTAKA IHYA’ ULUMUDDIN) - Muhammad Hambal Shafwan; M. Arfan Mu'ammar; Abdul Basit (Program Studi Pendidikan Agama Islam, 2023)
This research was conducted because of the background of problems that occur in today’s society, especially the education mobilizers, it was stated that various ways have been carried out to cultivate the religious character of students, but it had not been achieved properly. This research hoped to be one of the solutions in growing the religious character of students, in addition to the formulation and research on growing religious character continues to be sustainable. The formulation of the problem of this thesis is First, how is the concept of fasting in the perspective of al-Ghazali (study of the literature of Ihya' Ulumuddin), Second, how is the concept of fasting of the perspective of al-Ghazali in cultivating the religious character of the learners (study of the library of Ihya' Ulumuddin). This type of researcher was a quantifiable researcher of literature review that collects primary data through the direct work of al-Ghazali, namely Ihya’ Ulumuddin, there was seconder data in the form of regular which was a supporter of secondary data such as the book of Bidayatu al-Hidayah, after all the data were collected in the continuation of the analysis in a descriptive manner and described in a descriptive form. The results concluded that the concept of fasting al-Ghazali in cultivating the religious character of students of the Ihya’ Ulumuddin literature study must meet the aspects of birth and inner aspects which then these two aspects can foster religious character such as an attitude of tolerance, peace-loving, firm stance, sincere, confident and cooperation between followers of religion and belief. Keywords: Fasting, al-Ghazali, Religious Character, Learners, and Ihya’ Ulumuddin.